Antistatic heat-insulating coating and preparation method thereof

By using Vitrimer xylose polyacrylate and antistatic heat insulation composite materials in antistatic insulation coatings, combined with specific feeding sequence and preparation methods, the problem of insufficient performance of existing coatings is solved, and the paint has high mechanical properties, thermal stability and good antistatic and thermal insulation properties are achieved.

CN119614003AActive Publication Date: 2025-03-14DALIAN UNIV +1

Patent Information

Application Number
CN202510157696.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-13
Publication Date
2025-03-14
Estimated Expiration
2045-02-13

AI Technical Summary

Technical Problem

Existing anti-static insulating coatings have not yet met the high requirements in terms of anti-static properties, thermal insulation properties, mechanical properties and heat resistance, and there are few products that have both the above properties.

Method used

The formulation of an antistatic insulating coating is adopted, including polyacrylate, titanium dioxide, antistatic insulating fillers, hydrophilic aerogels, diatomaceous earth, defoaming agents, film forming additives, dispersants and water. The polyacrylate uses Vitrimer xylose polyacrylate with a specific structure to ensure uniform dispersion of components through a specific feeding sequence and preparation method to avoid the formation of particles or blocks.

Benefits of technology

It significantly improves the mechanical properties of the paint (such as hardness, adhesion, wear resistance, etc.), thermal stability and durability, meet the application scenarios of high temperature and high mechanical performance requirements, and also has good anti-static and thermal insulation properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119614003A_ABST
    Figure CN119614003A_ABST
Patent Text Reader

Abstract

The invention provides an antistatic heat-insulating coating and a preparation method thereof, and relates to the technical field of coatings. The antistatic heat-insulating coating is prepared from polyacrylate, titanium dioxide, antistatic heat-insulating filler, hydrophilic aerogel, diatomite, water and other raw materials, the polyacrylate comprises Vitrimer xylose polyacrylate with a specific structure, the Vitrimer xylose polyacrylate is used as a substrate material of the coating, and the mechanical property, heat resistance, durability and the like of the coating can be remarkably improved; furthermore, the antistatic heat-insulating filler comprises an antistatic heat-insulating composite material which is formed by compounding a light material, polypyrrole and a carbon material, the composite material is prepared by an in-situ polymerization method, and a unique structure that a composite microlayer is formed by compounding the polypyrrole and the carbon material on the surface of the light material is formed; the anti-static heat-insulating composite material and other raw materials in the coating cooperate with each other to act together, so that the prepared coating has good anti-static performance and heat-insulating performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of coatings, and in particular relates to an antistatic thermal insulation coating and a preparation method thereof. Background Art

[0002] Antistatic thermal insulation coating is a special coating that combines antistatic function and thermal insulation performance. The antistatic function means that it can effectively conduct electricity and prevent the potential safety hazards caused by static electricity accumulation, which is particularly important for the storage and transportation of flammable and explosive items. The thermal insulation performance means that the coating can reduce heat conduction, help maintain a stable temperature in the internal environment, and reduce energy consumption. The above characteristics make antistatic thermal insulation coatings widely used in many fields such as electronic equipment, construction, automobiles, and aerospace.

[0003] With the development of science and technology and the increase in applications, the requirements for the antistatic performance, thermal insulation performance, mechanical properties and heat resistance of antistatic thermal insulation coatings are becoming higher and higher. However, among the current coating products, there are still few products that have both the above properties and can meet the higher use requirements, so the antistatic performance, thermal insulation performance, mechanical properties, heat resistance and other properties of coatings need to be further improved.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] The present invention aims to provide an antistatic heat-insulating (thermal insulation) coating and a preparation method and coating to improve one of the above-mentioned problems existing in the prior art.

[0006] In order to achieve the above purpose, the following technical solutions are adopted: The first object of the present invention is to provide an antistatic thermal insulation coating, wherein the total mass of the antistatic thermal insulation coating is 100%, and the antistatic thermal insulation coating comprises the following components in mass fractions: Polyacrylate 30%-40%, titanium dioxide 10%-15%, antistatic heat insulation filler 0.2%-3%, hydrophilic aerogel 0.1%-0.2%, diatomaceous earth 1%-4%, defoamer 1%-4%, film-forming aid 1%-5%, dispersant 0.1%-1.5% and water 30%-55%; Further, on the basis of the above technical solution of the present invention, the polyacrylate includes Vitrimer xylose polyacrylate, and the structural formula of Vitrimer xylose polyacrylate is specifically shown in formula (a): (a); In formula (a), R is selected from an alkyl group having 1 to 3 carbon atoms.

[0007] Further, based on the above technical solution of the present invention, the preparation method of Vitrimer xylose polyacrylate comprises the following steps: S1. Mixing an alcohol solution containing xylose and acryloyl chloride and reacting them under the action of an alkaline catalyst to obtain xylose acrylate; S2. xylose acrylate, acrylate monomer, initiator and solvent are mixed and polymerized under nitrogen atmosphere, and a precipitation promoting agent is added to the obtained polymerization product to precipitate xylose polyacrylate generated by the polymerization reaction, and then filtered, washed and dried to obtain xylose polyacrylate; S3. Xylose polyacrylate and 2,2'-dithiodiethanol are mixed and reacted under the action of a crosslinking agent to obtain Vitrimer xylose polyacrylate.

[0008] Further, based on the above technical solution of the present invention, the molecular weight of Vitrimer xylose polyacrylate is 10000-150000 g / mol.

[0009] Further, based on the above technical solution of the present invention, in step S1, the mass ratio of xylose and acryloyl chloride in the alcohol solution containing xylose is (1-3): (1-3); and / or, in step S1, the alkaline catalyst comprises sodium hydroxide; and / or, in step S1, the reaction temperature is 50-100° C. and the reaction time is 2-6 h; and / or, in step S2, the molar ratio of xylose acrylate to acrylate monomer is (1-3): (1-3); And / or, in step S2, the polymerization reaction temperature is 50-100° C., the reaction time is 2-10 h, and the polymerization reaction is terminated by adding a terminator, hydroquinone; and / or, in step S3, the molar ratio of xylose polyacrylate to 2,2'-dithiodiethanol is (1-4):(2-4); and / or, in step S3, the cross-linking agent comprises cystamine; And / or, in step S3, the reaction temperature is 50-100° C. and the reaction time is 2-6 h.

[0010] Further, on the basis of the above technical solution of the present invention, the antistatic heat-insulating filler includes an antistatic heat-insulating composite material, which is mainly composed of a lightweight material, polypyrrole and a carbon material. The composite material is prepared by an in-situ polymerization method and has a structure of a composite microlayer of polypyrrole and carbon material on the surface of a lightweight material; The lightweight material includes at least one of aerogel, hollow glass microspheres, expanded microspheres, floating beads or perlite; The carbon material includes at least one of carbon nanotubes, modified products of carbon nanotubes, graphene or modified products of graphene.

[0011] Furthermore, based on the above technical solution of the present invention, the lightweight material includes at least one of aerogel, hollow glass microspheres or expanded microspheres.

[0012] Further, based on the above technical solution of the present invention, the carbon material includes carbon nanotubes and / or graphene oxide; And / or, the mass ratio of the lightweight material, polypyrrole and carbon material is (1.2-1.5):(0.5-0.8):(0.08-0.2).

[0013] Furthermore, based on the above technical solution of the present invention, a method for preparing the antistatic heat-insulating composite material comprises the following steps: (a) providing a pyrrole aqueous solution, a ferric chloride p-toluenesulfonic acid mixed solution and a carbon material dispersion; (b) The lightweight material is mixed with the pyrrole aqueous solution, and then the ferric chloride p-toluenesulfonic acid mixed solution and the carbon material dispersion are added to carry out a polymerization reaction. After the reaction is completed, the obtained product is subjected to solid-liquid separation, and the separated solid product is dried to obtain an antistatic heat-insulating composite material composed of the lightweight material, polypyrrole and carbon material.

[0014] Further, based on the above technical solution of the present invention, in step (a), the molar concentration of pyrrole in the pyrrole aqueous solution is 0.1M-0.8M; And / or, in the ferric chloride-toluenesulfonic acid mixed solution, the molar concentration of ferric chloride is 0.1M-0.8M, and the molar concentration of p-toluenesulfonic acid is 0.1M-0.8M; And / or, the mass concentration of the carbon material in the carbon material dispersion is 1-10 mg / ml.

[0015] Further, based on the above technical solution of the present invention, in step (b), the mass ratio of the lightweight material to the mass ratio of the pyrrole aqueous solution is 5-10%; and / or, the total mass ratio of ferric chloride and p-toluenesulfonic acid in the ferric chloride and p-toluenesulfonic acid mixed solution to the mass ratio of the pyrrole aqueous solution is 45-60%; and / or, the mass ratio of the carbon material dispersion to the pyrrole aqueous solution is 5-15%; And / or, the polymerization reaction temperature is 15-30°C, and the polymerization reaction time is 1-3h; And / or, the drying is vacuum drying, and the vacuum drying temperature is 50-90°C.

[0016] Further, on the basis of the above technical solution of the present invention, the hydrophilic aerogel comprises silica aerogel; and / or, the defoamer comprises at least one of n-butanol, an organosilicon defoamer or a polyether defoamer; and / or, the film-forming aid comprises at least one of ethylene glycol, propylene glycol butyl ether, hydrocarbons or dodecyl alcohol ester; And / or, the dispersant includes at least one of SN5040 dispersant, a cationic wetting dispersant or a nonionic dispersant.

[0017] The second object of the present invention is to provide a method for preparing the above-mentioned antistatic thermal insulation coating, comprising the following steps: Titanium dioxide, hydrophilic aerogel, diatomaceous earth and a portion of the water are stirred and mixed once to obtain a mixed solution I; Adding a part of the formula amount of the defoamer and a part of the formula amount of the film-forming aid to the mixed solution I and stirring and mixing them for a second time to obtain a mixed solution II; Adding polyacrylate to the mixed solution II and stirring and mixing for three times to obtain a mixed solution III; Add a dispersion formed by an antistatic thermal insulation filler and the remaining amount of water, a dispersant, a remaining amount of a defoamer and a remaining amount of a film-forming aid to the mixed solution III and stir and mix four times to obtain an antistatic thermal insulation coating.

[0018] Further, based on the above technical solution of the present invention, the time of stirring and mixing is 1-10min, and the stirring speed is 500-800r / min; And / or, the secondary stirring and mixing time is 10-30 min, and the stirring speed is 500-800 r / min; And / or, the three stirring and mixing times are 30-60 min, and the stirring speed is 500-800 r / min; And / or, the time of the four stirring and mixing is 60-120 min, and the stirring speed is 450-750 r / min.

[0019] The third object of the present invention is to provide a coating, which is formed by coating the antistatic thermal insulation coating provided by the first object of the present invention or the antistatic thermal insulation coating prepared by the preparation method provided by the second object of the present invention.

[0020] Compared with the prior art, the technical solution of the present invention has at least the following technical effects: (1) The present invention provides an antistatic thermal insulation coating, which is mainly made of raw materials such as polyacrylate, titanium dioxide, antistatic thermal insulation filler, hydrophilic aerogel, diatomaceous earth, defoaming agent, film-forming aid, dispersant and water, wherein the polyacrylate includes Vitrimer xylose polyacrylate with a specific structure. The xylose structure and disulfide bond are simultaneously introduced into the structure of Vitrimer xylose polyacrylate, which can improve the mechanical properties and heat resistance of the polymer itself, thereby significantly improving the mechanical properties (hardness, adhesion, wear resistance, etc.), thermal stability and durability of the coating (coating).

[0021] (2) The present invention also provides a method for preparing the above-mentioned antistatic thermal insulation coating. By adopting a specific adding sequence, the coating can be well dispersed and is not easy to form particles or lumps, which is beneficial to improving the overall performance of the coating.

[0022] (3) The present invention also provides an antistatic heat-insulating composite material, which is a composite of a lightweight material, polypyrrole and a carbon material to form a unique structure of a composite microlayer of a composite conductive polymer (polypyrrole) and a carbon material on the surface of the lightweight material. The synergistic effect of the three materials and the specific composite structure formed make the composite material have good heat-insulating and antistatic properties, and can be used as an antistatic heat-insulating filler for coatings (especially antistatic heat-insulating coatings); Furthermore, the antistatic thermal insulation composite material provided by the present invention is used as an antistatic thermal insulation filler, and cooperates with other raw materials such as polyacrylate to make the prepared antistatic thermal insulation coating have both good antistatic and thermal insulation properties, which can meet the different needs of various application scenarios.

[0023] (4) The present invention also provides a method for preparing an antistatic heat-insulating composite material, which realizes the composite of a lightweight material, polypyrrole and a carbon material by an in-situ polymerization method, thereby forming a unique structure of a composite microlayer of a conductive polymer (polypyrrole) and a carbon material on the surface of the lightweight material; in addition, the in-situ polymerization technology can form a thin and uniform conductive polymer (polypyrrole), so when polymerizing the lightweight material, the carbon material and pyrrole, the polypyrrole and the carbon material can be effectively polymerized on the surface of the lightweight material, thereby enhancing the common properties of the materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The figure is a schematic diagram of the preparation process of the antistatic heat-insulating composite material and the antistatic heat-insulating coating of the present invention; Figure 2 The SEM images of the antistatic heat-insulating composite material (HPG) provided in Example 1 of the present invention at different scanning magnifications, wherein (a) the scanning magnification is 100 times, and (b) the scanning magnification is 450 times; Figure 3The SEM images of the antistatic heat-insulating composite material (TPG) provided in Example 2 of the present invention at different scanning magnifications, wherein (a) the scanning magnification is 100 times, and (b) the scanning magnification is 450 times; Figure 4 The SEM images of the antistatic thermal insulation coating (P-HPG) provided in Example 3 of the present invention at different scanning magnifications, wherein (a) the scanning magnification is 100 times, and (b) the scanning magnification is 450 times; Figure 5 The SEM images of the antistatic thermal insulation coating (P-TPG) provided in Example 7 of the present invention at different scanning magnifications, wherein (a) the scanning magnification is 100 times, and (b) the scanning magnification is 450 times; Figure 6 Infrared spectra of the antistatic thermal insulation coatings provided in Examples 3 to 6 of the present invention and Comparative Example 1; Figure 7 Infrared spectra of the antistatic thermal insulation coatings provided in Examples 7 to 10 of the present invention and Comparative Example 2; Figure 8 The heat insulation temperature difference performance diagram of the antistatic heat insulation coating provided in Examples 3 to 6 of the present invention and Comparative Example 1 after 60 minutes; Fig. 9 This is a thermal insulation temperature difference performance diagram of the antistatic thermal insulation coating provided in Examples 7 to 10 of the present invention and Comparative Example 2 after 60 minutes; Fig.10 A graph showing the antistatic resistance values ​​of the antistatic thermal insulation coatings provided in Examples 3 to 6 of the present invention and Comparative Example 1; Fig.11 A graph showing the antistatic resistance values ​​of the antistatic thermal insulation coatings provided in Examples 7 to 10 of the present invention and Comparative Example 2; Fig.12 A comparison chart of the adhesion of the antistatic thermal insulation coatings provided in Examples 3 to 6 of the present invention and Comparative Example 1; Fig.13 A comparison chart of the adhesion of the antistatic thermal insulation coatings provided in Examples 7 to 10 of the present invention and Comparative Example 2; Fig.14 is the infrared spectrum of Vitrimer xylose polyacrylate in Examples 11 and 12 of the present invention; Fig.15 This is a heat resistance comparison chart of the Vitrimer xylose polyacrylate provided by the present invention and conventional polyacrylate. DETAILED DESCRIPTION

[0025] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme in the embodiment of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention. The process parameters of the following embodiments that do not specify specific conditions are usually based on conventional conditions.

[0026] The endpoints and any values ​​of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in the present invention.

[0027] According to a first aspect of the present invention, an antistatic heat-insulating composite material is provided. The composite material is mainly composed of a lightweight material, polypyrrole and a carbon material. The composite material is prepared by an in-situ polymerization method and has a structure of a composite microlayer of polypyrrole and carbon material on the surface of the lightweight material. The lightweight material includes at least one of aerogel, hollow glass microspheres, expanded microspheres, floating beads or perlite; The carbon material includes at least one of carbon nanotubes, modified products of carbon nanotubes, graphene, or modified products of graphene (eg, graphene oxide).

[0028] Specifically, the lightweight material of the present invention is usually selected from lightweight, porous materials with thermal insulation properties. Among them, aerogel has the characteristics of improving the thermal insulation performance of coatings, reducing coating density, enhancing the adhesion, anti-permeability and durability of coatings, and improving construction performance. Its role in antistatic thermal insulation composite materials is to improve thermal insulation performance and enhance adhesion; hollow glass microspheres have the functions of reducing weight, improving dielectric properties, improving flow properties, reducing oil absorption, reducing volume costs and heat insulation, etc., and have the function of heat insulation in antistatic thermal insulation composite materials; expanded microspheres have the functions of enhancing the mechanical properties of materials, improving strength and durability, as well as heat insulation, shock absorption and flame retardancy, and mainly play the role of heat insulation and enhancing the durability of materials in antistatic thermal insulation composite materials; floating beads have the functions of heat insulation and enhancing adhesion, and have the function of improving coating adhesion in antistatic thermal insulation coatings; perlite mainly plays the role of improving durability and coating adhesion in antistatic thermal insulation composite materials.

[0029] Polypyrrole has the characteristics of conductivity, stability, porosity and strong processing performance, and has the function of increasing the adhesion of materials in antistatic thermal insulation composite materials.

[0030] Among carbon materials, carbon nanotube modified products and / or graphene modified products refer to products after the structure or surface of carbon nanotubes and / or graphene is modified to improve their own performance (such as dispersibility or compatibility, etc.). Carbon materials have low cost, good corrosion resistance, and excellent electrical conductivity. Adding them to antistatic and thermal insulation composite materials can improve the electrical conductivity of the composite materials. At the same time, their water dispersibility can be improved by modifying the structure or surface. The amount added to the polymer matrix material (such as polyacrylate) of the subsequent coating is less, and the conductive and mechanical properties of the formed coating are more excellent.

[0031] The antistatic heat-insulating composite material of the present invention is formed by compounding a lightweight material, polypyrrole and a carbon material to form a unique structure of a composite microlayer of a composite conductive polymer (polypyrrole) and a carbon material on the surface of the lightweight material. The synergistic effect of the three materials and the specific composite structure formed make the composite material have good heat-insulating and antistatic properties, and can be used as an antistatic heat-insulating filler for coatings (especially antistatic heat-insulating coatings).

[0032] As a preferred embodiment of the technical solution of the present invention, the carbon material includes carbon nanotubes and / or graphene oxide. The carbon material is selected from carbon nanotubes, graphene oxide, etc., which is conducive to further improving the electronic conduction, mechanical and aging resistance of the coating. A small amount of addition can effectively improve the conductivity, impact resistance and aging resistance of the polymer material.

[0033] As an optional implementation of the technical solution of the present invention, the mass ratio between the lightweight material, polypyrrole and carbon material is (1.2-1.5): (0.5-0.8): (0.08-0.2), preferably (1.2-1.4): (0.5-0.7): (0.1-0.2), and more preferably 1.3: 0.6: 0.1. When the mass ratio between the lightweight material, polypyrrole and carbon material is within the above-mentioned specific range, it is beneficial for the polypyrrole and carbon material to be better composited on the lightweight material, maximizing the composite efficiency and thus reducing unnecessary waste of materials, and the formed composite material is better dispersed in the coating as an antistatic and thermal insulation filler, which helps to improve the antistatic and thermal insulation properties of the coating. When the mass ratio between the lightweight material, polypyrrole and carbon material is not within the above-mentioned specific range, it is not conducive to the polypyrrole and carbon material to be better composited on the lightweight material, or when there is too much carbon material, the color of the coating will become irreversible black, thereby limiting the application of the coating. Therefore, typical but non-limiting mass ratios of lightweight material, polypyrrole and carbon material are 1.2:0.5:0.08, 1.2:0.5:0.1, 1.2:0.5:0.15, 1.2:0.5:0.2, 1.2:0.6:0.1, 1.2:0.6:0.2, 1.2:0.7:0.1, 1.2:0.7:0.2, 1.2:0.8:0.1, 1.2:0.8:0.2, 1.3:0.5:0.08, 1.3:0.5:0.1, 1.3:0 .5:0.2, 1.3:0.6:0.1, 1.3:0.6:0.2, 1.3:0.7:0.1, 1.3:0.7:0.2, 1.3:0.8:0.1, 1.3:0.8:0.2, 1.4:0.5:0.08, 1.4:0.6:0.1, 1.4:0.7:0.1, 1.4:0.8:0.2, 1.5:0.6:0.1, 1.5:0.6:0.2, 1.5:0.7:0.2 or 1.5:0.8:0.2, etc.

[0034] By further limiting the mass ratio of each component in the antistatic thermal insulation composite material, the lightweight material is composited more evenly with the polypyrrole and carbon material, thereby better improving the thermal insulation and antistatic properties of the coating.

[0035] According to a second aspect of the present invention, there is provided a method for preparing the above antistatic heat-insulating composite material, comprising the following steps: (a) providing a pyrrole aqueous solution, a ferric chloride p-toluenesulfonic acid mixed solution and a carbon material dispersion; (b) The lightweight material is mixed with the pyrrole aqueous solution, and then the ferric chloride p-toluenesulfonic acid mixed solution and the carbon material dispersion are added to carry out a polymerization reaction. After the reaction is completed, the obtained product is subjected to solid-liquid separation, and the separated solid product is dried to obtain an antistatic heat-insulating composite material composed of the lightweight material, polypyrrole and carbon material. The process flow diagram is shown in FIG. Figure 1 shown.

[0036] Specifically, the ferric chloride-toluenesulfonic acid mixed solution mainly uses ferric chloride as an oxidant and p-toluenesulfonic acid (TsOH) as a dopant, which is beneficial to the in-situ polymerization of pyrrole.

[0037] This preparation method realizes the composite of lightweight material, polypyrrole and carbon material by in-situ polymerization, forming a unique structure of composite microlayer of composite conductive polymer (polypyrrole) and carbon material on the surface of lightweight material. Through the synergistic effect between the three materials and the specific composite structure formed, the composite material has good thermal insulation and antistatic properties, and can be used as antistatic thermal insulation filler for coatings (especially antistatic thermal insulation coatings). The composite material prepared by this method has excellent mechanical properties and interface strength, which can enhance the effect of polypyrrole and carbon materials on coatings and improve their comprehensive performance. In addition, the in-situ polymerization technology can form a thin and uniform polymer electrolyte (polypyrrole), so when polymerizing lightweight materials, carbon materials and pyrrole, polypyrrole and carbon materials can be effectively polymerized on the surface of lightweight materials to enhance the common properties of the materials.

[0038] As an optional implementation of the technical solution of the present invention, in step (a), the pyrrole aqueous solution is prepared by mixing water (such as deionized water) with pyrrole, and then ultrasonicating the mixed solution in an ultrasonic instrument for 15-30 minutes (such as 15 minutes, 20 minutes, 25 minutes or 30 minutes, etc.) to fully mix the water and pyrrole.

[0039] As an optional implementation of the technical solution of the present invention, in step (a), the molar concentration of pyrrole in the pyrrole aqueous solution is 0.1M-0.8M; typical but non-limiting molar concentrations are 0.1M, 0.2M, 0.3M, 0.4M, 0.5M, 0.6M, 0.7M or 0.8M, etc.

[0040] As an optional implementation of the technical solution of the present invention, in step (a), the preparation of a mixed solution of ferric chloride and p-toluenesulfonic acid: water (such as deionized water) is mixed with ferric chloride and p-toluenesulfonic acid to prepare a mixed solution of ferric chloride and p-toluenesulfonic acid with a molar concentration of 0.1-0.8M.

[0041] As an optional embodiment of the technical solution of the present invention, in step (a), in the ferric chloride and p-toluenesulfonic acid mixed solution, the molar concentration of ferric chloride is 0.1M-0.8M, and the molar concentration of p-toluenesulfonic acid is 0.1M-0.8M. The typical but non-limiting molar concentration of ferric chloride is 0.1M, 0.2M, 0.3M, 0.4M, 0.5M, 0.6M, 0.7M or 0.8M, etc. The typical but non-limiting molar concentration of p-toluenesulfonic acid is 0.1M, 0.2M, 0.3M, 0.4M, 0.5M, 0.6M, 0.7M or 0.8M, etc.

[0042] As an optional implementation of the technical solution of the present invention, in step (a), the method for preparing the carbon material dispersion includes: mixing the carbon material with water (e.g., deionized water), and then ultrasonically dispersing the mixture for 20-40 minutes (e.g., 20 minutes, 25 minutes, 30 minutes, 35 minutes or 40 minutes, etc.) to obtain the carbon material dispersion.

[0043] As an optional implementation scheme of the technical solution of the present invention, in step (a), the mass concentration of the carbon material in the carbon material dispersion is 1-10 mg / ml, and a typical but non-limiting mass concentration is 1 mg / ml, 2 mg / ml, 5 mg / ml, 6 mg / ml, 8 mg / ml or 10 mg / ml, etc.

[0044] As an optional implementation of the technical solution of the present invention, in step (b), the mass ratio of the lightweight material to the mass ratio of the pyrrole aqueous solution is 5%-10%, and a typical but non-limiting mass ratio is 5%, 6%, 7%, 8%, 9% or 10%, etc.

[0045] As an optional embodiment of the technical solution of the present invention, in step (b), the total mass ratio of ferric chloride and p-toluenesulfonic acid in the ferric chloride p-toluenesulfonic acid mixed solution to the pyrrole aqueous solution is 45-60%. Typical but non-limiting mass ratios are 45%, 48%, 50%, 52%, 55%, 58% or 60%, etc.

[0046] As an optional implementation of the technical solution of the present invention, in step (b), the mass ratio of the carbon material dispersion to the pyrrole aqueous solution is 5-15%, and a typical but non-limiting mass ratio is 5%, 6%, 7%, 8%, 9%, 10%, 12%, 14% or 15%, etc.

[0047] By limiting the concentrations of the pyrrole aqueous solution, the ferric chloride-toluenesulfonic acid mixed solution, and the carbon material dispersion, as well as the relative amounts of the lightweight material and the above solutions or dispersions, the mass ratio of each component in the obtained antistatic heat-insulating composite material is within a specific numerical range, so that pyrrole can be more effectively polymerized into the antistatic material polypyrrole, and better composited with the carbon material on the lightweight material.

[0048] The polymerization reaction conditions of the present invention do not need to be too harsh and can usually be completed at room temperature. As an optional implementation of the technical solution of the present invention, in step (b), the polymerization reaction temperature is 15-30°C, and the polymerization reaction time is 1-3h. Typical but non-limiting polymerization reaction temperatures are 15°C, 18°C, 20°C, 25°C, 28°C or 30°C, etc., and typical but non-limiting times are 1h, 1.5h, 2h, 2.5h or 3h, etc. The above reaction conditions are mild and easy to implement.

[0049] As an optional implementation of the technical solution of the present invention, in step (b), the drying is vacuum drying, and the vacuum drying temperature is 50-90°C. Typical but non-limiting vacuum drying temperatures are 50°C, 60°C, 70°C, 80°C or 90°C, etc.

[0050] According to a third aspect of the present invention, there is also provided an antistatic thermal insulation (insulation) coating, which comprises the following components in mass fractions, based on the total mass of the antistatic thermal insulation coating being 100%: Polyacrylate 30%-40%, titanium dioxide 10%-15%, antistatic heat insulation filler 0.2%-3%, hydrophilic aerogel 0.1%-0.2%, diatomaceous earth 1%-4%, defoamer 1%-4%, film-forming aid 1%-5%, dispersant 0.1%-1.5% and water 30%-55%; Among them, polyacrylate is mainly used as the base material of the antistatic thermal insulation coating to form a film. The polyacrylate can be a conventional polyacrylate emulsion in the art. Preferably, the polyacrylate includes Vitrimer xylose polyacrylate, which is first proposed by the inventor and has a structural formula as shown in formula (a): (a); In formula (a), R is selected from an alkyl group having 1 to 3 carbon atoms, such as -CH3, -CH2CH3 or -CH2CH2CH3.

[0051] The inventors have found through a lot of practice that when part or all of the polyacrylate in the coating uses Vitrimer xylose polyacrylate with a specific structure, the mechanical properties (such as strength, adhesion, hardness, wear resistance, etc.) and thermal stability of the antistatic thermal insulation coating are significantly improved, which is mainly due to the introduction of xylose structure and disulfide bonds. Among them, the introduction of xylose structure can significantly enhance the bio-based characteristics, mechanical properties, thermal stability, etc. of the polymer. When the Vitrimer xylose polyacrylate containing xylose structure is used as the base material of the coating, the strength, adhesion, hardness and thermal stability of the coating (coating) are significantly improved relative to conventional polyacrylates. At the same time, since the xylose structure is derived from a bio-based material, it is harmless to nature and has a low cost, so the Vitrimer xylose polyacrylate made from it is also more environmentally friendly, and it also reduces the production cost of Vitrimer xylose polyacrylate.

[0052] The disulfide bonds have high thermal stability and can remain stable within a certain temperature range, which can improve the thermal stability and heat resistance of Vitrimer xylose polyacrylate. At the same time, the introduction of disulfide bonds can increase the cross-linking density of Vitrimer xylose polyacrylate, thereby improving its mechanical properties, such as strength, hardness, adhesion and wear resistance (durability).

[0053] In view of the above-mentioned characteristics of xylose structure and disulfide bonds, when Vitrimer xylose polyacrylate is used as the base material of the coating, the mechanical properties such as strength, hardness, adhesion, wear resistance and thermal stability of the coating can be significantly improved, making the coating more suitable for application scenarios with high temperature and high mechanical performance requirements (such as heat-resistant coatings, heat-resistant composite materials, etc.).

[0054] Typical but non-limiting mass fractions of polyacrylate are 30%, 32%, 34%, 35%, 36%, 38% or 40%, etc.

[0055] The main functions of titanium dioxide in antistatic thermal insulation coatings are whitening, improving hiding power, enhancing light resistance and weather resistance, etc. As a pigment, titanium dioxide has a high refractive index, strong tinting power and good hiding power, which can make the color of the coating more vivid and enhance the overall visual effect of the product. In addition, titanium dioxide can also enhance its adhesion in the coating, prevent the coating from sagging, and has a UV shielding function to protect the coating from UV damage. Typical but non-restrictive mass fractions of titanium dioxide are 10%, 11%, 12%, 13%, 14% or 15%, etc.

[0056] The antistatic thermal insulation filler mainly adopts raw materials that can further enhance the antistatic ability and thermal insulation performance of the coating. Preferably, the functional material adopts the antistatic thermal insulation composite material provided by the first aspect of the present invention. Since the antistatic thermal insulation composite material itself has excellent electrical conductivity, when it is added to the coating, a conductive network can be formed in the coating, which can effectively reduce the resistivity of the coating, thereby preventing the accumulation and discharge of static electricity. At the same time, since the antistatic thermal insulation composite material also has good thermal insulation performance, it is added to the coating as an antistatic thermal insulation filler, which can not only increase the antistatic ability of the coating, but also improve the thermal insulation performance of the coating. The mass fraction of the antistatic thermal insulation filler should not be too low (less than 0.2%), otherwise it will easily lead to a decrease in thermal insulation and antistatic properties. The mass fraction of antistatic thermal insulation filler should not be too high (higher than 3%), otherwise it will easily cause the coating to crack and fall off after drying and film formation. Therefore, the typical but non-restrictive mass fraction of antistatic thermal insulation filler is 0.2%, 0.4%, 0.5%, 0.6%, 0.8%, 1.0%, 1.2%, 1.4%, 1.5%, 1.6%, 1.8%, 2%, 2.2%, 2.4%, 2.5%, 2.6%, 2.8% or 3.0%, etc.

[0057] The main function of the hydrophilic aerogel in the antistatic thermal insulation coating is to improve the thermal insulation performance of the coating. The typical but non-limiting mass fraction of the hydrophilic aerogel is 0.1%, 0.12%, 0.14%, 0.15%, 0.18% or 0.2%, etc.

[0058] Diatomaceous earth is mainly used as a filler in antistatic thermal insulation coatings. Its porosity can effectively remove harmful substances in the air. The typical but non-limiting mass fraction of diatomaceous earth is 1%, 1.5%, 2%, 2.5%, 3%, 3.5% or 4%, etc.

[0059] In addition to adding the above-mentioned main ingredients, a certain amount of functional additives, such as defoaming agents, film-forming agents or dispersants, etc., also need to be added.

[0060] Typical but non-limiting mass fractions of defoamers are 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, or 4%, etc. Typical but non-limiting mass fractions of film-forming aids are 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, or 5%, etc. Typical but non-limiting mass fractions of dispersants are 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.4%, or 1.5%, etc.

[0061] The antistatic thermal insulation coating provided by the present invention is mainly made of raw materials such as polyacrylate, titanium dioxide, antistatic thermal insulation filler, hydrophilic aerogel, diatomaceous earth, defoamer, film-forming aid, dispersant and water. Preferably, the polyacrylate includes Vitrimer xylose polyacrylate with a specific structure. The xylose structure and disulfide bond are simultaneously introduced into the structure of Vitrimer xylose polyacrylate, which can improve the mechanical strength, hardness, adhesion and heat resistance of the polymer itself, thereby significantly improving the mechanical properties, thermal stability and durability of the coating (coating); and / or, the antistatic thermal insulation filler is the antistatic thermal insulation composite material provided by the first aspect of the present invention or the antistatic thermal insulation composite material prepared by the method of the second aspect.

[0062] Furthermore, the present invention adopts an antistatic thermal insulation composite material as an antistatic thermal insulation filler. The antistatic thermal insulation filler cooperates with other raw materials such as polyacrylate to make the prepared coating have good antistatic performance and thermal insulation performance, which can meet the needs of application scenarios with high requirements for antistatic performance and thermal insulation performance.

[0063] As a preferred implementation mode of the technical solution of the present invention, based on the total mass of the antistatic thermal insulation coating as 100%, the antistatic thermal insulation coating includes the following components in mass fractions: 35%-40% polyacrylate, 12%-15% titanium dioxide, 0.5%-2.5% antistatic thermal insulation filler, 0.1%-0.2% hydrophilic aerogel, 2%-4% diatomaceous earth, 2%-4% defoaming agent, 2%-5% film-forming aid, 0.5%-1.5% dispersant, and the balance is made up of water.

[0064] As an optional implementation of the technical solution of the present invention, the hydrophilic aerogel includes silica aerogel.

[0065] As an optional implementation of the technical solution of the present invention, the defoaming agent includes at least one of n-butanol, silicone defoaming agent or polyether defoaming agent, and is preferably n-butanol.

[0066] As an optional implementation of the technical solution of the present invention, the film-forming aid includes at least one of ethylene glycol, propylene glycol butyl ether, hydrocarbons or dodecyl alcohol esters, and is preferably ethylene glycol.

[0067] As an optional implementation of the technical solution of the present invention, the dispersant includes at least one of SN5040 dispersant, a cationic wetting dispersant or a non-ionic dispersant, preferably SN5040 dispersant.

[0068] The polyacrylate in the coating can be all Vitrimer xylose polyacrylate with a specific cross-linked structure, or part of it can be Vitrimer xylose polyacrylate and the other part can be conventional polyacrylate commercially available in the art. As a preferred embodiment of the technical solution of the present invention, the polyacrylate is Vitrimer xylose polyacrylate.

[0069] As an optional implementation of the technical solution of the present invention, the preparation method of Vitrimer xylose polyacrylate comprises the following steps: S1. Mixing an alcohol solution containing xylose and acryloyl chloride, and reacting them under the action of an alkaline catalyst, the specific reaction formula is shown in formula (1), to obtain xylose acrylate; (1); S2. xylose acrylate, acrylate monomer, initiator and solvent are mixed and polymerized under nitrogen atmosphere. The specific reaction formula is shown in formula (2) to obtain a polymerization product. Adding a precipitation-promoting agent to the obtained polymerization product to precipitate the xylose polyacrylate generated by the polymerization reaction in the form of a precipitate, and then filtering, washing and drying to obtain the xylose polyacrylate; (2); S3. Xylose polyacrylate and 2,2'-dithiodiethanol are mixed and reacted under the action of a crosslinking agent. The specific reaction formula is shown in formula (3), thereby obtaining Vitrimer xylose polyacrylate.

[0070] (3); In step S3, dithiodiethanol can react with the hydroxyl group in the polymer (xylose polyacrylate) chain through its disulfide bond to introduce the disulfide bond into the main chain or side chain to form a cross-linked structure. Among them, 2,2'-dithiodiethanol can be purchased or prepared by itself. Taking self-preparation as an example, the following description is given: a. Select sulfur-containing monomers: Use monomers with thiol groups (-SH), such as dimercaptoethanol; b. Oxidation reaction: The thiol groups on the monomers with thiol groups are oxidized to form disulfide bonds. Commonly used oxidants include oxygen, hydrogen peroxide or iodine. The reaction conditions need to be mild to avoid destroying other functional groups, for example, as shown in formula (4): (4).

[0071] As an optional implementation of the technical solution of the present invention, in step S1, the mass ratio of xylose and acryloyl chloride in the alcohol solution containing xylose is (1-3): (1-3), for example, 1:1, 1:2, 1:3, 2:1, 2:3, 3:1 or 3:2; and / or, in step S1, the alkaline catalyst comprises sodium hydroxide; And / or, in step S1, the reaction temperature is 50-100°C, for example, 50°C, 60°C, 70°C, 80°C, 90°C or 100°C, preferably 60°C, and the reaction time is 2-6h, for example, 2h, 3h, 4h, 5h or 6h, etc.

[0072] As an optional implementation of the technical solution of the present invention, in step S2, the molar ratio of xylose acrylate to acrylate monomer is (1-3): (1-3), for example, 1:1, 1:2, 1:3, 2:1, 2:3, 3:1 or 3:2, etc., preferably 1:1; And / or, in step S2, the polymerization reaction temperature is 50-100°C, for example, 50°C, 60°C, 70°C, 80°C, 90°C or 100°C, etc., preferably 60°C, the reaction time is 2-10h, for example, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h or 10h, etc., and the polymerization reaction is terminated by adding a terminator such as hydroquinone.

[0073] As an optional implementation of the technical solution of the present invention, in step S3, the molar ratio of xylose polyacrylate to 2,2'-dithiodiethanol is (1-4): (2-4), for example, 1:2, 1:3, 1:4, 2:2, 2:3, 2:4, 3:2, 3:4, 4:2 or 4:3, etc.; and / or, in step S3, the cross-linking agent comprises cystamine; And / or, in step S3, the reaction temperature is 50-100°C, for example, 50°C, 60°C, 70°C, 80°C, 90°C or 100°C, and the reaction time is 2-6h, for example, 2h, 3h, 4h, 5h or 6h, etc. There is no specific limitation on the molecular weight of Vitrimer xylose polyacrylate. The mechanical properties and thermal stability of the polymer can be adjusted by adjusting the structure and proportion of structural units such as xylose and acrylate structures according to actual needs, so that it can meet the needs of more different application scenarios. As an optional implementation of the technical solution of the present invention, the molecular weight of Vitrimer xylose polyacrylate is 10000-150000 g / mol, for example, 10000 g / mol, 40000 g / mol, 50000 g / mol, 80000 g / mol, 100000 g / mol, 120000 g / mol, 140000 g / mol or 150000 g / mol, etc.

[0074] As an optional implementation of the technical solution of the present invention, the antistatic resistance value of the antistatic thermal insulation coating is 10 6 -10 9 Ω, for example, 10 6 Ω, 10 7 Ω, 10 8 Ω or 10 9 Ω, etc., preferably 10 6 -10 8 Ω.

[0075] According to a fourth aspect of the present invention, there is also provided a method for preparing the antistatic thermal insulation coating, comprising the following steps: Titanium dioxide, hydrophilic aerogel, diatomaceous earth and a portion of the water are stirred and mixed once to obtain a mixed solution I; Adding a part of the formula amount of the defoamer and a part of the formula amount of the film-forming aid to the mixed solution I and stirring and mixing them for a second time to obtain a mixed solution II; Adding polyacrylate to the mixed solution II and stirring and mixing for three times to obtain a mixed solution III; Add the dispersion formed by the antistatic heat-insulating filler and the remaining amount of water, the dispersant, the remaining amount of the defoamer and the remaining amount of the film-forming aid to the mixed solution III and stir and mix four times to obtain the antistatic heat-insulating coating. The preparation process diagram is shown in FIG. Figure 1 shown.

[0076] The preparation method of the antistatic thermal insulation coating provided by the present invention adopts a specific material addition sequence, which is conducive to the coating being well dispersed and not easy to form particles or lumps, and is conducive to improving the overall performance of the coating.

[0077] As an optional implementation of the technical solution of the present invention, the time for a stirring and mixing is 1-10 minutes, and the stirring speed is 500-800 r / min. Typical but non-limiting stirring and mixing times are 1 minute, 2 minutes, 3 minutes, 5 minutes, 6 minutes, 8 minutes or 10 minutes, and typical but non-limiting stirring speeds are 500 r / min, 550 r / min, 600 r / min, 650 r / min, 700 r / min, 750 r / min or 800 r / min, etc.

[0078] As an optional implementation of the technical solution of the present invention, the secondary stirring and mixing time is 10-30 minutes, and the stirring speed is 500-800 r / min. Typical but non-limiting secondary stirring and mixing time is 10 minutes, 15 minutes, 20 minutes, 25 minutes, 28 minutes or 30 minutes, and the typical but non-limiting stirring speed is 500 r / min, 550 r / min, 600 r / min, 650 r / min, 700 r / min, 750 r / min or 800 r / min, etc.

[0079] As an optional implementation of the technical solution of the present invention, the time for the three stirring and mixing is 30-60 minutes, and the stirring speed is 500-800 r / min. Typical but non-limiting three stirring and mixing times are 30 minutes, 35 minutes, 40 minutes, 45 minutes, 50 minutes, 55 minutes or 60 minutes, etc., and typical but non-limiting stirring speeds are 500 r / min, 550 r / min, 600 r / min, 650 r / min, 700 r / min, 750 r / min or 800 r / min, etc.

[0080] As an optional implementation of the technical solution of the present invention, the time for the four stirring and mixing is 60-120 minutes, and the stirring speed is 450-750 r / min. Typical but non-limiting four stirring and mixing times are 60 minutes, 70 minutes, 80 minutes, 90 minutes, 100 minutes, 110 minutes or 120 minutes, etc., and typical but non-limiting stirring speeds are 450 r / min, 500 r / min, 550 r / min, 600 r / min, 650 r / min, 700 r / min or 750 r / min, etc.

[0081] According to the fifth aspect of the present invention, there is also provided a coating, which is formed by coating the antistatic thermal insulation coating provided by the third aspect of the present invention or the antistatic thermal insulation coating prepared by the preparation method provided by the fourth aspect of the present invention.

[0082] The coating provided by the present invention can be a single-layer coating or a multi-layer coating. The multi-layer coating can be obtained by coating the antistatic thermal insulation coating of the present invention multiple times, or the antistatic thermal insulation coating of the present invention can be used as a primer and other coating compositions can be used as a topcoat, or other coating compositions can be used as a primer and the antistatic thermal insulation coating of the present invention can be used as a topcoat.

[0083] The coating provided by the present invention not only has good antistatic and heat insulation properties, but also has good mechanical properties such as adhesion with the substrate (base material) or primer, and is not prone to peeling off after long-term use.

[0084] The present invention is further described in detail below in conjunction with specific examples and comparative examples. It should be noted that in the following examples and comparative examples, the density of the defoaming agent n-butanol is 0.808 g / ml, the density of the film-forming aid ethylene glycol is 1.111 g / ml, and the density of the dispersant SN5040 is 1.25 g / cm 3 .

[0085] Example 1 This embodiment provides an antistatic heat-insulating composite material (hollow glass microspheres / polypyrrole / graphene oxide, abbreviated as HPG), which is mainly composed of a lightweight material, polypyrrole and a carbon material; Among them, the lightweight material is hollow glass microspheres (average particle size 80μm), the carbon material is graphene oxide (sheet diameter 60-200nm), and the mass ratio of the lightweight material, polypyrrole and carbon material is 1.3:0.6:0.1.

[0086] This embodiment provides a method for preparing an antistatic heat-insulating composite material, comprising the following steps: S1. Preparation of pyrrole aqueous solution: Add 50 ml of deionized water and 1750 μl of pyrrole into a clean beaker, and ultrasonicate the mixed solution for 15 min using an ultrasonic instrument to fully mix the water and pyrrole to obtain a pyrrole aqueous solution with a molar concentration of 0.5 M.

[0087] S2. Preparation of ferric chloride p-toluenesulfonic acid solution: weigh 13.52 g of ferric chloride and 9.51 g of p-toluenesulfonic acid in a beaker, add 40 ml of water to dissolve, pour into a 100 ml volumetric flask and make up to volume to obtain 100 ml of ferric chloride p-toluenesulfonic acid solution, in which the molar concentration of ferric chloride is 0.5 M, and the molar concentration of p-toluenesulfonic acid is 0.5 M.

[0088] S3. Carbon material dispersion: A graphene oxide aqueous dispersion in a liquid state is used, and the concentration of graphene oxide in the graphene oxide aqueous dispersion is 2 mg / mL.

[0089] S4. In-situ polymerization of pyrrole: Weigh 3g of hollow glass microspheres and put them into the pyrrole aqueous solution and stir them evenly in a magnetic stirrer for 30min. Then, take 50ml of the mixed solution of ferric chloride and p-toluenesulfonic acid and slowly pour it into the pyrrole aqueous solution. Then, add 6mL of graphene oxide aqueous dispersion and slowly stir it on the stirrer at room temperature (15-25℃) for 2h to carry out the polymerization reaction. After the reaction is completed, take out the sample and filter the water with a vacuum pump. Then, dry it in a vacuum drying oven at 70℃. After drying, grind the sample into powder (particle size is 50-90μm) to obtain an antistatic thermal insulation composite material.

[0090] Example 2 This embodiment provides an antistatic heat-insulating composite material (expanded microspheres / polypyrrole / graphene oxide, abbreviated as TPG), the composite material is mainly composed of a lightweight material, polypyrrole and a carbon material; Among them, the lightweight material is expanded microspheres (particle size range is 15-25μm), the carbon material is graphene oxide (sheet diameter is 60-200nm), and the mass ratio of the lightweight material, polypyrrole and carbon material is 1.3:0.6:0.1.

[0091] The preparation method of the antistatic heat-insulating composite material of this embodiment is the same as that of Example 1 except that the hollow glass microspheres in the preparation method of Example 1 are replaced by expanded microspheres. Other raw materials, amounts and preparation methods are the same as those of Example 1.

[0092] Example 3 This embodiment provides an antistatic thermal insulation coating (abbreviated as P-HPG (2.0)), which includes the following components in mass fractions, based on the total mass of the antistatic thermal insulation coating being 100%: Polyacrylate 38.7%, titanium dioxide 13.2%, antistatic thermal insulation filler 2.0%, hydrophilic aerogel 0.2%, diatomaceous earth 3.1%, defoaming agent 3.3%, film-forming aid 4.5%, dispersant 1.3%, and water makes up the balance.

[0093] Among them, the antistatic thermal insulation composite material provided in Example 1 is used as the antistatic thermal insulation filler, the polyacrylate is a polyacrylate with a solid content of 55% (acrylate copolymer emulsion, purchased from Jiangsu Sanmu Group Co., Ltd., product brand: Sanmu® SM-100), the hydrophilic aerogel is a silica aerogel (particle size range is 15-50 μm), the defoaming agent is n-butanol, the film-forming aid is ethylene glycol, and the dispersant is SN5040 dispersant.

[0094] The preparation method of the antistatic heat-insulating coating comprises the following steps: (a) Weigh 13 g of titanium dioxide, 0.2 g of hydrophilic aerogel, and 3 g of diatomaceous earth, pour them into a three-necked flask in sequence, add 23 mL of deionized water, and then turn on the stirrer to stir and mix for 10 minutes at a stirring speed of 650 r / min to obtain a mixed solution I; (b) Add 2 mL of defoamer and 2 mL of film-forming aid to the mixed solution I, and stir for a second time (at high speed) for 30 minutes at a stirring speed of 650 r / min to obtain a mixed solution II; (c) Add 38 mL of polyacrylate to the mixed solution II, and stir and mix three times (at a low speed). After stirring and dispersing for 60 minutes, the stirring speed is 450 r / min to obtain a mixed solution III. (d) Add 2.0 g of antistatic thermal insulation filler to the mixed solution III. The antistatic thermal insulation filler needs to be added after ultrasonic dispersion with 10 mL of deionized water. Finally, add 1 mL of dispersant, 2 mL of defoaming agent and 2 mL of film-forming aid. Stir at a low speed for 120 minutes. The stirring speed is 450 r / min. Pour it out to obtain the antistatic thermal insulation coating (about 98.1 g).

[0095] Example 4 This embodiment provides an antistatic thermal insulation coating (abbreviated as P-HPG (1.5)), which includes the following components in mass fractions, based on the total mass of the antistatic thermal insulation coating being 100%: Polyacrylate 38.7%, titanium dioxide 13.2%, antistatic thermal insulation filler 1.5%, hydrophilic aerogel 0.2%, diatomaceous earth 3.1%, defoaming agent 3.3%, film-forming aid 4.5%, dispersant 1.3%, and water makes up the balance.

[0096] Among them, the antistatic thermal insulation composite material provided in Example 1 is used as the antistatic thermal insulation filler, the polyacrylate is a polyacrylate with a solid content of 55% (acrylate copolymer emulsion, purchased from Jiangsu Sanmu Group Co., Ltd., product brand: Sanmu® SM-100), the hydrophilic aerogel is a silica aerogel (particle size range is 15-50 μm), the defoaming agent is n-butanol, the film-forming aid is ethylene glycol, and the dispersant is SN5040 dispersant.

[0097] The preparation method of the antistatic thermal insulation coating is the same as that of Example 3, except that the amount of the antistatic thermal insulation filler is adjusted from 2.0 g to 1.5 g in step (d), and the amount of deionized water is adjusted accordingly so that the total mass of the antistatic thermal insulation coating remains unchanged. The remaining raw materials, amounts and preparation method are the same as those of Example 3.

[0098] Example 5 This embodiment provides an antistatic thermal insulation coating (abbreviated as P-HPG (1.0)), which includes the following components in mass fractions, based on the total mass of the antistatic thermal insulation coating being 100%: Polyacrylate 38.7%, titanium dioxide 13.2%, antistatic thermal insulation filler 1.0%, hydrophilic aerogel 0.2%, diatomaceous earth 3.1%, defoamer 3.3%, film-forming aid 4.5%, dispersant 1.3%, and water makes up the balance.

[0099] Among them, the antistatic thermal insulation composite material provided in Example 1 is used as the antistatic thermal insulation filler, the polyacrylate is a polyacrylate with a solid content of 55% (acrylate copolymer emulsion, purchased from Jiangsu Sanmu Group Co., Ltd., product brand: Sanmu® SM-100), the hydrophilic aerogel is a silica aerogel (particle size range is 15-50 μm), the defoaming agent is n-butanol, the film-forming aid is ethylene glycol, and the dispersant is SN5040 dispersant.

[0100] The preparation method of the antistatic thermal insulation coating is the same as that of Example 3, except that the amount of the antistatic thermal insulation filler is adjusted from 2.0 g to 1.0 g in step (d), and the amount of deionized water is adjusted accordingly so that the total mass of the antistatic thermal insulation coating remains unchanged. The remaining raw materials, amounts and preparation method are the same as those of Example 3.

[0101] Example 6 This embodiment provides an antistatic thermal insulation coating (abbreviated as P-HPG (0.5)), which includes the following components in mass fractions, based on the total mass of the antistatic thermal insulation coating being 100%: Polyacrylate 38.7%, titanium dioxide 13.2%, antistatic thermal insulation filler 0.5%, hydrophilic aerogel 0.2%, diatomaceous earth 3.1%, defoamer 3.3%, film-forming aid 4.5%, dispersant 1.3%, and water makes up the balance.

[0102] Among them, the antistatic thermal insulation composite material provided in Example 1 is used as the antistatic thermal insulation filler, the polyacrylate is a polyacrylate with a solid content of 55% (acrylate copolymer emulsion, purchased from Jiangsu Sanmu Group Co., Ltd., product brand: Sanmu® SM-100), the hydrophilic aerogel is a silica aerogel (particle size range is 15-50 μm), the defoaming agent is n-butanol, the film-forming aid is ethylene glycol, and the dispersant is SN5040 dispersant.

[0103] The preparation method of the antistatic thermal insulation coating is the same as that of Example 3, except that the amount of the antistatic thermal insulation filler is adjusted from 2.0 g to 0.5 g in step (d), and the amount of deionized water is adjusted accordingly so that the total mass of the antistatic thermal insulation coating remains unchanged. The remaining raw materials, amounts and preparation method are the same as those of Example 3.

[0104] Example 7 This embodiment provides an antistatic thermal insulation coating (abbreviated as P-TPG (2.0)), which includes the following components in mass fractions, based on the total mass of the antistatic thermal insulation coating being 100%: Polyacrylate 38.7%, titanium dioxide 13.2%, antistatic thermal insulation filler 2%, hydrophilic aerogel 0.2%, diatomaceous earth 3.1%, defoamer 3.3%, film-forming aid 4.5%, dispersant 1.3%, and water makes up the balance.

[0105] Among them, the antistatic thermal insulation composite material provided in Example 2 is used as the antistatic thermal insulation filler, the polyacrylate is a polyacrylate with a solid content of 55% (acrylate copolymer emulsion, purchased from Jiangsu Sanmu Group Co., Ltd., product brand: Sanmu® SM-100), the hydrophilic aerogel is a silica aerogel (particle size range is 15-50 μm), the defoaming agent is n-butanol, the film-forming aid is ethylene glycol, and the dispersant is SN5040 dispersant.

[0106] The preparation method of the antistatic thermal insulation coating is the same as that of Example 3, except that in step (d), the type of the antistatic thermal insulation filler is adjusted from the antistatic thermal insulation composite material HPG provided in Example 1 to the antistatic thermal insulation composite material TPG provided in Example 2, the mass of the antistatic thermal insulation filler is still 2.0 g, and the remaining raw materials, amounts and preparation method are the same as those of Example 3.

[0107] Example 8 This embodiment provides an antistatic thermal insulation coating (abbreviated as P-TPG (1.5)), which includes the following components in mass fractions, based on the total mass of the antistatic thermal insulation coating being 100%: Polyacrylate 38.7%, titanium dioxide 13.2%, antistatic thermal insulation filler 1.5%, hydrophilic aerogel 0.2%, diatomaceous earth 3.1%, defoamer 3.3%, film-forming aid 4.5%, dispersant 1.3%, and water makes up the balance.

[0108] Among them, the antistatic thermal insulation composite material provided in Example 2 is used as the antistatic thermal insulation filler, the polyacrylate is a polyacrylate with a solid content of 55% (acrylate copolymer emulsion, purchased from Jiangsu Sanmu Group Co., Ltd., product brand: Sanmu® SM-100), the hydrophilic aerogel is a silica aerogel (particle size range is 15-50 μm), the defoaming agent is n-butanol, the film-forming aid is ethylene glycol, and the dispersant is SN5040 dispersant.

[0109] The preparation method of the antistatic thermal insulation coating is the same as that of Example 7, except that the amount of the antistatic thermal insulation filler is adjusted from 2.0 g to 1.5 g in step (d), and the amount of deionized water is adjusted accordingly to keep the total mass of the antistatic thermal insulation coating unchanged.

[0110] Example 9 This embodiment provides an antistatic thermal insulation coating (abbreviated as P-TPG (1.0)), which includes the following components in mass fractions, based on the total mass of the antistatic thermal insulation coating being 100%: Polyacrylate 38.7%, titanium dioxide 13.2%, antistatic thermal insulation filler 1.0%, hydrophilic aerogel 0.2%, diatomaceous earth 3.1%, defoamer 3.3%, film-forming aid 4.5%, dispersant 1.3%, and water makes up the balance.

[0111] Among them, the antistatic thermal insulation composite material provided in Example 2 is used as the antistatic thermal insulation filler, the polyacrylate is a polyacrylate with a solid content of 55% (acrylate copolymer emulsion, purchased from Jiangsu Sanmu Group Co., Ltd., product brand: Sanmu® SM-100), the hydrophilic aerogel is a silica aerogel (particle size range is 15-50 μm), the defoaming agent is n-butanol, the film-forming aid is ethylene glycol, and the dispersant is SN5040 dispersant.

[0112] The preparation method of the antistatic thermal insulation coating is the same as that of Example 7, except that the amount of the antistatic thermal insulation filler is adjusted from 2.0 g to 1.0 g in step (d), and the amount of deionized water is adjusted accordingly to keep the total mass of the antistatic thermal insulation coating unchanged.

[0113] Example 10 This embodiment provides an antistatic thermal insulation coating (abbreviated as P-TPG (0.5)), which includes the following components in mass fractions, based on the total mass of the antistatic thermal insulation coating being 100%: Polyacrylate 38.7%, titanium dioxide 13.2%, antistatic thermal insulation filler 0.5%, hydrophilic aerogel 0.2%, diatomaceous earth 3.1%, defoamer 3.3%, film-forming aid 4.5%, dispersant 1.3%, and water makes up the balance.

[0114] Among them, the antistatic thermal insulation composite material provided in Example 2 is used as the antistatic thermal insulation filler, the polyacrylate is a polyacrylate with a solid content of 55% (acrylate copolymer emulsion, purchased from Jiangsu Sanmu Group Co., Ltd., product brand: Sanmu® SM-100), the hydrophilic aerogel is a silica aerogel (particle size range is 15-50 μm), the defoaming agent is n-butanol, the film-forming aid is ethylene glycol, and the dispersant is SN5040 dispersant.

[0115] The preparation method of the antistatic thermal insulation coating is the same as that of Example 7, except that the amount of the antistatic thermal insulation filler is adjusted from 2.0 g to 0.5 g in step (d), and the amount of deionized water is adjusted accordingly so that the total mass of the antistatic thermal insulation coating remains unchanged.

[0116] Embodiment 11 This embodiment provides an antistatic thermal insulation coating, except that the type of polyacrylate in Example 5 (P-HPG (1.0)) is replaced by Vitrimer xylose polyacrylate from polyacrylate with a solid content of 55% (acrylate copolymer emulsion, purchased from Jiangsu Sanmu Group Co., Ltd., product brand: Sanmu® SM-100), and the remaining raw materials, amounts and preparation methods are the same as those in Example 5.

[0117] The structural formula of Vitrimer xylose polyacrylate in this embodiment is as follows: , wherein R is -CH3.

[0118] The preparation method of Vitrimer xylose polyacrylate comprises the following steps: S1. 3 g of xylose was placed in a 100 mL three-necked flask and dissolved in 12 mL of ethanol solvent to obtain an alcohol solution containing xylose; The alcohol solution containing xylose and 4 mL of acryloyl chloride were mixed, and 0.03 g of alkaline catalyst sodium hydroxide was added, and the mixture was stirred to react at a temperature of 60° C. for 4 h to obtain xylose acrylate; S2. Mix 20.41g xylose acrylate (0.1mol) and 8.609g methyl acrylate monomer (0.1mol) in a three-necked flask at a molar ratio of 1:1, add an appropriate amount of water as a solvent and stir evenly, then add 0.2g initiator benzoyl peroxide to the reaction solution, raise the reaction temperature to 60°C, and react for 6h. During the reaction, nitrogen needs to be passed to avoid contact with oxygen. When the reaction time is reached, the terminator hydroquinone needs to be added to terminate the polymerization reaction, and the reaction mixture is poured into a large amount of non-solvent methanol or acetone to precipitate the polymer. The precipitate is filtered and washed to remove the unreacted monomer and initiator, and the polymer is dried in a vacuum oven to obtain xylose polyacrylate; S3. 20.18g xylose polyacrylate (0.1mol) and 30.85g 2,2'-dithiodiethanol (0.2mol) were mixed and reacted under the action of 0.1g crosslinking agent cystamine at a reaction temperature of 60°C for 6h to obtain Vitrimer xylose polyacrylate. The molecular weight of Vitrimer xylose polyacrylate was about 80,000.

[0119] Example 12 This embodiment provides an antistatic thermal insulation coating, except that the type of polyacrylate in Example 9 (P-TPG (1.0)) is replaced by Vitrimer xylose polyacrylate (structure and specific preparation method are the same as those in Example 11) from polyacrylate with a solid content of 55% (acrylate copolymer emulsion, purchased from Jiangsu Sanmu Group Co., Ltd., product brand: Sanmu® SM-100), the remaining raw materials, amounts and preparation methods are the same as those in Example 9.

[0120] Comparative Example 1 This comparative example provides an antistatic thermal insulation coating (abbreviated as PHPG), which includes the following components in mass fractions, based on the total mass of the antistatic thermal insulation coating as 100%: Polyacrylate 38.7%, titanium dioxide 13.2%, hollow glass microspheres 1.3%, graphene oxide 0.1%, polypyrrole 0.6%, hydrophilic aerogel 0.2%, diatomaceous earth 3.1%, defoamer 3.3%, film-forming aid 4.5%, dispersant 1.3%, and water makes up the balance.

[0121] Among them, hollow glass microspheres, graphene oxide, and polypyrrole are used together as antistatic thermal insulation fillers, polyacrylate is polyacrylate with a solid content of 55% (acrylate copolymer emulsion), the hydrophilic aerogel is silica aerogel (particle size range is 15-50μm), the defoaming agent is n-butanol, the film-forming aid is ethylene glycol, and the dispersant is SN5040 dispersant.

[0122] The preparation method of the antistatic heat-insulating coating comprises the following steps: (a) Weigh 13 g of titanium dioxide, 0.2 g of hydrophilic aerogel, and 3 g of diatomaceous earth, pour them into a three-necked flask in sequence, add 23 mL of deionized water, and then turn on the stirrer to stir and mix for 10 minutes at a stirring speed of 650 r / min to obtain a mixed solution I; (b) Add 2 mL of defoamer and 2 mL of film-forming aid to the mixed solution I, and stir for a second time (at high speed) for 30 minutes at a stirring speed of 650 r / min to obtain a mixed solution II; (c) Add 38 mL of polyacrylate to the mixed solution II, and stir and mix three times (at a low speed). After stirring and dispersing for 60 minutes, the stirring speed is 450 r / min to obtain a mixed solution III. (d) Add 0.1 g of graphene oxide, 0.6 g of polypyrrole and 1.3 g of hollow glass microspheres as antistatic thermal insulation fillers to the mixed solution III. The antistatic thermal insulation filler needs to be ultrasonically dispersed with 10 mL of deionized water before adding. Finally, add 1 mL of dispersant, 2 mL of defoaming agent and 2 mL of film-forming aid. Stir at low speed for 120 minutes. The stirring speed is 450 r / min, and pour out to obtain the preparation method of antistatic thermal insulation coating.

[0123] Comparative Example 2 This comparative example provides an antistatic thermal insulation coating (abbreviated as THPG), which includes the following components in mass fractions, based on the total mass of the antistatic thermal insulation coating as 100%: Polyacrylate 38.7%, titanium dioxide 13.2%, expanded microspheres 1.3%, graphene oxide 0.1%, polypyrrole 0.6%, hydrophilic aerogel 0.2%, diatomaceous earth 3.1%, defoamer 3.3%, film-forming aid 4.5%, dispersant 1.3%, and water makes up the balance.

[0124] Among them, expanded microspheres, graphene oxide, and polypyrrole are used together as antistatic thermal insulation fillers, polyacrylate is polyacrylate with a solid content of 55% (acrylate copolymer emulsion), the hydrophilic aerogel is silica aerogel (particle size range is 15-50μm), the defoaming agent is n-butanol, the film-forming aid is ethylene glycol, and the dispersant is SN5040 dispersant.

[0125] The preparation method of the antistatic thermal insulation coating is the same as that of Comparative Example 1, except that 0.1 g of graphene oxide, 0.6 g of polypyrrole and 1.3 g of expanded microspheres are used as antistatic thermal insulation fillers in step (d). Other raw materials, amounts and preparation methods are the same as those of Comparative Example 1.

[0126] In order to compare the technical effects of the above embodiments and comparative examples, the following experimental examples are specially set up. It should be noted that in the experimental results, P-HPG (2.0), P-HPG (1.5), P-HPG (1.0), P-HPG (0.5) and PHPG refer to the antistatic thermal insulation coatings provided in Example 3, Example 4, Example 5, Example 6 and Comparative Example 1, respectively. P-TPG (2.0), P-TPG (1.5), P-TPG (1.0), P-TPG (0.5) and PTPG refer to the antistatic thermal insulation coatings provided in Example 7, Example 8, Example 9, Example 10 and Comparative Example 2, respectively.

[0127] Experimental Example 1 The morphologies of the antistatic heat-insulating composite material (HPG) provided in Example 1 and the antistatic heat-insulating composite material (TPG) provided in Example 2 were detected, and their SEM images were as follows: Figure 2 and Figure 3 As shown. Figure 2 As can be seen in (a) and (b), polypyrrole and graphene oxide composites are aggregated on the surface of the hollow glass microspheres, which indicates that the in-situ composite is successful and the shape is basically spherical. Figure 3 As can be seen in (a) and (b), polypyrrole and graphene oxide composites are also aggregated on the surface of the expanded microspheres, indicating that the in situ composite is successful and the shape is basically spherical.

[0128] Taking the antistatic thermal insulation coating (P-HPG) provided in Example 3 and the antistatic thermal insulation coating (P-TPG) provided in Example 7 as examples, their morphologies were detected, and their SEM images were as follows: Figure 4 and Figure 5 As shown. Figure 4 and Figure 5 It can be seen that the composite formed by hollow glass microspheres or expanded microspheres, polypyrrole and graphene oxide is encapsulated inside the polyacrylate. After magnification 450 times, protruding hollow glass microspheres or expanded microspheres can be seen on the surface, indicating that the hollow glass microsphere polymer and the expanded microsphere polymer are evenly dispersed inside the coating.

[0129] Experimental Example 2 (1) The antistatic thermal insulation coatings provided in Examples 3 to 6 and Comparative Example 1 were used as a comparison group, and the antistatic thermal insulation coatings provided in Examples 7 to 10 and Comparative Example 2 were used as a comparison group, and their infrared spectra were detected respectively. Figure 6 shown.

[0130] from Figure 6 In the infrared spectrum, graphene oxide has a peak at 3357 cm -1 There is a strong and broad absorption peak at 1725cm -1 It is attributed to the C=O stretching vibration peak. 1650cm -1 It is the stretching vibration peak of C=C; 1034cm -1 The stretching vibration peak attributed to -CH is derived from the characteristic peak of polypyrrole, 2950cm -1 Attributed to -CH2 stretching vibration peak; 1147cm -1 The stretching vibration peak attributed to CO is a characteristic peak of polyacrylate. -1 The C=C characteristic peak of the pyrrole ring and the OH characteristic peak of graphene oxide and the C=O stretching vibration peak can also be found in the comparison sample PHPG.

[0131] from Figure 7 In the infrared spectrum, graphene oxide has a peak at 3357 cm -1 There is a strong and broad absorption peak at 1723cm-1 It is attributed to the C=O stretching vibration peak. 1650cm -1 It is the stretching vibration peak of C=C; 1040cm -1 The stretching vibration peak attributed to -CH comes from the infrared characteristic peak of polypyrrole. 2932cm -1 It is attributed to the -CH2 stretching vibration peak. 1162cm -1 It is attributed to CO, which is a characteristic peak of polyacrylate. From the figure, it can be seen that the characteristic peaks of carbon materials, polyacrylates and graphene oxide in the comparative sample also correspond to the characteristic peaks of the sample, indicating that the polymer materials of the comparative sample exist.

[0132] (2) The antistatic thermal insulation coatings provided in Examples 3 to 6 and Comparative Example 1 were used as a control group, and the antistatic thermal insulation coatings provided in Examples 7 to 10 and Comparative Example 2 were used as a control group, and their thermal insulation temperature difference performance was tested. The specific testing method includes: (1) Two homemade insulation boxes, the insulation boxes have a temperature display and there are 7×15cm tinplate-sized holes on the insulation boxes; (2) 7×15cm blank tinplate (blank sample) and tinplate coated with 6mm thick coating (coating sample) are placed on the insulation sealing box respectively; (3) Irradiate with a 350W infrared lamp, record the temperature of the blank sample and the coating sample every 5 minutes, stop the infrared lamp irradiation after 1 hour, and calculate the reference temperature. Reference temperature calculation method: subtract the temperature of the coating sample from the temperature of the blank sample to get the temperature difference. The specific results are as follows: Figure 8 and Fig. 9 shown.

[0133] from Figure 8 and Fig. 9 It can be seen that by increasing the amount of in-situ polymerized antistatic thermal insulation filler HPG or TPG, the thermal insulation performance of the coating can be improved to a certain extent, and compared with PHPG or PTPG directly filled with polypyrrole, hollow glass microspheres or expanded microspheres, and graphene oxide coating samples, the antistatic thermal insulation coating (P-HPG or P-TPG) introduced with antistatic thermal insulation filler HPG or TPG of the present invention has better thermal insulation performance.

[0134] (3) The antistatic thermal insulation coatings provided in Examples 3 to 6 and Comparative Example 1 were used as a control group, and the antistatic thermal insulation coatings provided in Examples 7 to 10 and Comparative Example 2 were used as a control group, and their antistatic properties were tested in accordance with the ASTM standard D-257 test method. The specific results are as follows: Fig.10 and Fig.11 shown.

[0135] from Fig.10 and Fig.11It can be seen that the antistatic resistance values ​​of Comparative Example 1 (PHPG) are higher than those of Examples 3 to 6, and the antistatic resistance values ​​of Comparative Example 2 (PTPG) are higher than those of Examples 7 to 10. The larger the resistance value, the worse the antistatic effect, so the introduction of in-situ polymerized antistatic heat-insulating fillers is beneficial to increase the antistatic effect of the coating.

[0136] (4) The antistatic thermal insulation coatings provided in Examples 3 to 6 and Comparative Example 1 were used as a control group, and the antistatic thermal insulation coatings provided in Examples 7 to 10 and Comparative Example 2 were used as a control group to test their adhesion. The test method was based on GB / T 5210-2006 "Adhesion test of paint and varnish by pull-off method". The specific results are as follows: Fig.12 and Fig.13 shown.

[0137] from Fig.12 It can be seen that the adhesion of the coating with antistatic thermal insulation filler is basically better than that of the coating with the comparison sample PHPG. Since the polypyrrole is wrapped in the hollow glass microspheres through in-situ polymerization, the antistatic thermal insulation filler is better and more tightly attached to the base material polyacrylate, thereby effectively increasing its adhesion.

[0138] from Fig.13 It can be seen that the adhesion of coatings with different amounts of antistatic thermal insulation fillers added is different. The adhesion of coatings with antistatic thermal insulation fillers is basically better than that of coatings with the comparison sample PTPG. Since the polypyrrole is wrapped in the expanded microspheres through in-situ polymerization, the antistatic thermal insulation filler is better and more tightly adhered to the base material polyacrylate, thereby effectively increasing its adhesion.

[0139] (5) The antistatic thermal insulation coatings provided in Examples 3 to 6 and Comparative Example 1 were used as a control group, and the antistatic thermal insulation coatings provided in Examples 7 to 10 and Comparative Example 2 were used as a control group, and their hardness was tested. The specific detection method is based on GB / T 6739-1996 "Coating Hardness Pencil Determination Method". Hardness test standard: pencil numbers are 6H, 5H, 4H, 3H, 2H, H, F, HB, B, 2B, 3B, 4B, 5B, 6B, among which 6H is the hardest and 6B is the softest, and the hardness decreases from 6H to 6B. The specific results are shown in Tables 1 and 2.

[0140] Table 1 Table 2 Note: "+250g" means that the original test instrument is loaded with 250g, indicating that the hardness is one level higher.

[0141] From the hardness test data in Table 1 and Table 2, it can be seen that in Examples 3-6, when the amount of antistatic thermal insulation filler increases to 1g (corresponding to the composite material P-HPG (1.0)), the hardness reaches the highest, and the hardness of the coating with antistatic thermal insulation filler is basically higher than that of Comparative Example 1. It can be seen from Examples 7-10 that with the increase in the amount of antistatic thermal insulation filler, the hardness of the coating gradually increases, and is higher than that of Comparative Example 2. This also shows that coatings with different amounts of antistatic thermal insulation filler have different hardness levels, which can meet the needs of different application scenarios.

[0142] (6) The infrared spectra of the Vitrimer xylose polyacrylate in Example 11 and Example 12 were tested, as follows: Fig.14 shown.

[0143] from Fig.14 As can be seen, 1725cm -1 、1240-1260cm -1 and 1160-1180cm -1 These are the characteristic absorption peaks of polyacrylate. -1 The stretching vibration of C=O on the ester bond, 1240-1260cm -1 and 1160-1180cm -1 Represent the asymmetric and symmetric stretching vibrations of CO on the ester bond. 1020-1100 cm -1 and 3000-3600 cm -1 is the stretching vibration peak of the xylose structure, among which 1020-1100 cm -1 COC stretching vibration, 3000-3600 cm -1 The broader characteristic peak is the OH stretching vibration.

[0144] At the same time, in order to compare the performance of the Vitrimer xylose polyacrylate in Examples 11 and 12 with the conventional polyacrylate emulsion in Examples 3-10, the Vitrimer xylose polyacrylate and the conventional polyacrylate emulsion were coated on a substrate with the same surface roughness, and the coating area and coating thickness of the two were the same. The substrate samples of the Vitrimer xylose polyacrylate and the conventional polyacrylate emulsion after coating were placed in an oven at 100 o C drying for 12 hours, the substrate surface after drying is shown in the following figure Fig.15 As shown, Fig.15The substrate sample located above the picture is a substrate sample coated with a conventional polyacrylate emulsion, and the substrate sample located below the picture is a substrate sample coated with Vitrimer xylose polyacrylate. As can be seen from the figure, the surface of the substrate sample coated with conventional polyacrylate emulsion has obvious cracks, while the surface of the substrate sample coated with Vitrimer xylose polyacrylate is flat and intact without any cracks. It can be seen that the Vitrimer xylose polyacrylate provided by the present invention exhibits good mechanical strength and heat resistance, and its application in coatings (coatings) can also improve the mechanical properties and thermal stability of the coating.

[0145] In addition, Example 5 and Example 11 were used as a comparison group, and Example 9 and Example 12 were used as a comparison group to investigate the effect of the structure of polyacrylate on the coating performance from the aspects of adhesion and hardness. The adhesion test method is as described in Section (4) above, and the hardness test method and test standard are as described in Section (5) above, which will not be repeated here.

[0146] Table 3 From the data in Table 3, it can be seen that when Vitrimer xylose polyacrylate containing xylose structure is used as the base material of the coating, the adhesion and hardness performance of the coating (coating) are significantly improved compared with conventional polyacrylates, which is beneficial to extending the service life of the coating (coating).

[0147] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention are within the scope of protection of the pending claims of the present invention.

Claims

1. An antistatic thermal insulation coating, characterized in that: Taking the total mass of the antistatic thermal insulation coating as 100%, it includes the following components in mass fraction: Polyacrylate 30%-40%, titanium dioxide 10%-15%, antistatic heat insulation filler 0.2%-3%, hydrophilic aerogel 0.1%-0.2%, diatomaceous earth 1%-4%, defoamer 1%-4%, film-forming aid 1%-5%, dispersant 0.1%-1.5% and water 30%-55%; Wherein, the polyacrylate includes Vitrimer xylose polyacrylate, and the structural formula of Vitrimer xylose polyacrylate is specifically shown in formula (a): (a); In formula (a), R is selected from an alkyl group having 1 to 3 carbon atoms.

2. The antistatic thermal insulation coating according to claim 1, characterized in that: The preparation method of Vitrimer xylose polyacrylate comprises the following steps: S1. Mixing an alcohol solution containing xylose and acryloyl chloride and reacting them under the action of an alkaline catalyst to obtain xylose acrylate; S2. xylose acrylate, acrylate monomer, initiator and solvent are mixed and polymerized under nitrogen atmosphere, and a precipitation promoting agent is added to the obtained polymerization product to precipitate xylose polyacrylate generated by the polymerization reaction, and then filtered, washed and dried to obtain xylose polyacrylate; S3. Xylose polyacrylate and 2,2'-dithiodiethanol are mixed and reacted under the action of a crosslinking agent to obtain Vitrimer xylose polyacrylate.

3. The antistatic thermal insulation coating according to claim 2, characterized in that: In step S1, the mass ratio of xylose and acryloyl chloride in the alcohol solution containing xylose is (1-3): (1-3); and / or, in step S1, the alkaline catalyst comprises sodium hydroxide; and / or, in step S1, the reaction temperature is 50-100° C. and the reaction time is 2-6 h; and / or, in step S2, the molar ratio of xylose acrylate to acrylate monomer is (1-3): (1-3); And / or, in step S2, the polymerization reaction temperature is 50-100° C., the reaction time is 2-10 h, and the polymerization reaction is terminated by adding a terminator, hydroquinone; and / or, in step S3, the molar ratio of xylose polyacrylate to 2,2'-dithiodiethanol is (1-4):(2-4); and / or, in step S3, the cross-linking agent comprises cystamine; And / or, in step S3, the reaction temperature is 50-100° C. and the reaction time is 2-6 h.

4. The antistatic thermal insulation coating according to claim 1, characterized in that: The antistatic heat-insulating filler comprises an antistatic heat-insulating composite material, which is mainly composed of a lightweight material, polypyrrole and a carbon material. The composite material is prepared by an in-situ polymerization method and has a structure of a composite microlayer of polypyrrole and carbon material on the surface of the lightweight material; Wherein, the lightweight material comprises at least one of aerogel, hollow glass microspheres, expanded microspheres, floating beads or perlite; The carbon material includes at least one of carbon nanotubes, carbon nanotube modified products, graphene or graphene modified products; The mass ratio of the lightweight material, polypyrrole and carbon material is (1.2-1.5): (0.5-0.8): (0.08-0.2).

5. The antistatic thermal insulation coating according to claim 4, characterized in that: The preparation method of the antistatic heat-insulating composite material comprises the following steps: (a) providing a pyrrole aqueous solution, a ferric chloride p-toluenesulfonic acid mixed solution and a carbon material dispersion; (b) The lightweight material is mixed with the pyrrole aqueous solution, and then the ferric chloride p-toluenesulfonic acid mixed solution and the carbon material dispersion are added to carry out a polymerization reaction. After the reaction is completed, the obtained product is subjected to solid-liquid separation, and the separated solid product is dried to obtain an antistatic heat-insulating composite material composed of the lightweight material, polypyrrole and carbon material.

6. The antistatic thermal insulation coating according to claim 5, characterized in that: In step (a), the molar concentration of pyrrole in the pyrrole aqueous solution is 0.1M-0.8M; And / or, in step (a), in the ferric chloride and p-toluenesulfonic acid mixed solution, the molar concentration of ferric chloride is 0.1M-0.8M, and the molar concentration of p-toluenesulfonic acid is 0.1M-0.8M; And / or, in step (a), the mass concentration of the carbon material in the carbon material dispersion is 1-10 mg / ml; and / or, in step (b), the mass ratio of the lightweight material to the mass ratio of the pyrrole aqueous solution is 5-10%; And / or, in step (b), the total mass ratio of ferric chloride and p-toluenesulfonic acid in the ferric chloride and p-toluenesulfonic acid mixed solution to the mass ratio of the pyrrole aqueous solution is 45-60%; and / or, in step (b), the mass ratio of the carbon material dispersion to the pyrrole aqueous solution is 5-15%; And / or, in step (b), the polymerization reaction temperature is 15-30°C, and the polymerization reaction time is 1-3h; And / or, in step (b), the drying is vacuum drying, and the vacuum drying temperature is 50-90°C.

7. The antistatic thermal insulation coating according to any one of claims 1 to 6, characterized in that: The hydrophilic aerogel comprises silica aerogel; and / or, the defoamer comprises at least one of n-butanol, an organosilicon defoamer or a polyether defoamer; and / or, the film-forming aid comprises at least one of ethylene glycol, propylene glycol butyl ether, hydrocarbons or dodecyl alcohol ester; And / or, the dispersant includes at least one of SN5040 dispersant, a cationic wetting dispersant or a non-ionic dispersant.

8. The method for preparing the antistatic thermal insulation coating according to any one of claims 1 to 7, characterized in that: The following steps are involved: Titanium dioxide, hydrophilic aerogel, diatomaceous earth and a portion of the water are stirred and mixed once to obtain a mixed solution I; Adding a part of the formula amount of the defoamer and a part of the formula amount of the film-forming aid to the mixed solution I and stirring and mixing them for a second time to obtain a mixed solution II; Adding polyacrylate to the mixed solution II and stirring and mixing for three times to obtain a mixed solution III; Add a dispersion formed by an antistatic thermal insulation filler and the remaining amount of water, a dispersant, a remaining amount of a defoamer and a remaining amount of a film-forming aid to the mixed solution III and stir and mix four times to obtain an antistatic thermal insulation coating.

9. The method for preparing the antistatic thermal insulation coating according to claim 8, characterized in that: The mixing time is 1-10min, and the stirring speed is 500-800r / min; And / or, the secondary stirring and mixing time is 10-30 min, and the stirring speed is 500-800 r / min; And / or, the three stirring and mixing times are 30-60 min, and the stirring speed is 500-800 r / min; And / or, the time of the four stirring and mixing is 60-120 min, and the stirring speed is 450-750 r / min.

10. A coating, characterized in that: The antistatic thermal insulation coating is coated with the antistatic thermal insulation coating described in any one of claims 1 to 7 or the antistatic thermal insulation coating prepared by the preparation method described in claims 8 to 9.

Citation Information

Patent Citations

  • Thermal insulation paint and preparation method thereof

    CN105219232A

  • Epoxy resin paint with antistatic property and preparation method thereof

    CN106010118A

  • Recyclable castor oil-based unsaturated polyester Vitrimer material based on dynamic disulfide bond and preparation method of recyclable castor oil-based unsaturated polyester Vitrimer material

    CN113136105A

  • Fireproof thermal insulation coating based on aerogel

    CN116656194A

  • High performance and recyclable thermoset ink for 3D or 4d printing

    US20210122865A1

Cited By

  • Silicone rubber composite material for insulator and preparation method thereof

    CN121343366A